\(\frac{1}{3}x+650\%x-x=-6\)
\(\frac{1}{3}x+\frac{13}{2}x-x=-6\)
\(x\left(\frac{1}{3}+\frac{13}{2}-1\right)=-6\)
\(x\left(\frac{2}{6}+\frac{39}{6}-\frac{6}{6}\right)=-6\)
\(x\frac{35}{6}=-6\)
\(x=-6.\frac{35}{6}\)
\(x=-35\)
\(\Rightarrow x=-35\)
\(\frac{1}{3}x+650\%\cdot x-x=\left(-6\right)\)
\(\Rightarrow\frac{1}{3}x+6,5\cdot x-x=\left(-6\right)\)
\(\Rightarrow x\left(\frac{1}{3}+6,5-1\right)=\left(-6\right)\)
\(\Rightarrow x\left(\frac{1}{3}+\frac{13}{2}-1\right)=\left(-6\right)\)
\(\Rightarrow x\left(\frac{2}{6}+\frac{39}{6}-\frac{6}{6}\right)=\left(-6\right)\)
\(\Rightarrow x\left(\frac{2+39-6}{6}\right)=\left(-6\right)\)
\(\Rightarrow x\cdot\frac{35}{6}=\left(-6\right)\)
\(\Rightarrow x=\left(-6\right):\frac{35}{6}\)
\(\Rightarrow x=-\frac{36}{35}\)